2023
DOI: 10.1155/2023/8408574
|View full text |Cite
|
Sign up to set email alerts
|

TRIM72 Alleviates Muscle Inflammation in mdx Mice via Promoting Mitophagy-Mediated NLRP3 Inflammasome Inactivation

Abstract: Chronic muscle inflammation exacerbates the pathogenesis of Duchenne muscular dystrophy (DMD), which is characterized by progressive muscle degeneration and weakness. NLRP3 (nucleotide-binding domain and leucine-rich repeat pyrin domain containing 3) inflammasome plays a key role in the inflammatory process, and its abnormal activation leads to a variety of inflammatory or immune diseases. TRIM72 (MG53) is a protective myokine for tissue repair and regeneration. However, little is known about the potential imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…A previous study has indicated that TRIM72 attenuated LPS-induced neurotoxicity and neuroinflammation by inhibiting TLR4/NF-κB pathway both in vitro and in vivo [ 44 ]. A recent study has revealed that TRIM72 reduces muscle inflammation by promoting the inactivation of NLRP3 inflammasome [ 45 ]. Additionally, several studies have found a connection between TRIM72 and the influenza virus, demonstrating that TRIM72 protects mice from lethal influenza virus infection by suppressing interferon-β and inflammation [ 29 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has indicated that TRIM72 attenuated LPS-induced neurotoxicity and neuroinflammation by inhibiting TLR4/NF-κB pathway both in vitro and in vivo [ 44 ]. A recent study has revealed that TRIM72 reduces muscle inflammation by promoting the inactivation of NLRP3 inflammasome [ 45 ]. Additionally, several studies have found a connection between TRIM72 and the influenza virus, demonstrating that TRIM72 protects mice from lethal influenza virus infection by suppressing interferon-β and inflammation [ 29 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has indicated that TRIM72 attenuated LPS-induced neurotoxicity and neuroinflammation by inhibiting TLR4/NF-kB pathway both in vitro and in vivo [39]. A recent study has revealed that TRIM72 reduces muscle inflammation by promoting the inactivation of NLRP3 inflammasome [40]. Additionally, several studies have found a connection between TRIM72 and the influenza virus, demonstrating that TRIM72 protects mice from lethal influenza virus infection by suppressing inflammation [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria structure is altered even before the onset of muscle fiber damage and metabolic defects, lowered mitochondrial potential, and promoting excessive mtROS production [52]. In both DMD patients and animal models (mice and worms), autophagy and mitophagy appear to be significantly compromised, leading to the accumulation of damaged mitochondria that could negatively impact the muscle [53][54][55][56]. Interestingly, the inhibition of autophagy is evident with the progression of the disease, concomitant with the fibrotic phase and the exhaustion of stem-cell-mediated regeneration.…”
Section: Autophagy and Mitophagymentioning
confidence: 99%
“…Mitophagy is also impaired in DMD animal models, in mdx mice as well as dystrophic worms, and occurs in mature muscle fiber and muscle stem cells as well [55,64]. Mitophagy dysfunctions are associated with damage-associated molecular patterns (DAMPs) release, such as mtROS and mtDNA, which leads to activation of the NLRP3 inflammasome and promotes IL-1β and IL-18 secretion [54]. Accordingly, enhancing mitophagy by TRIM72 overexpression, a myokine with a protective role in tissue repair and regeneration, blunts the inflammasome increase and mitigates the inflammatory response, with positive effects in DMD [54].…”
Section: Autophagy and Mitophagymentioning
confidence: 99%